Hodnocení realitních investic s využitím softwarové podpory - Stehlík, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Práce se zabývá vyhodnocováním různých typů investic na realitním trhu, porovnává je z časového a finančního hlediska. Pro efektivní porovnávání je naprogramován kalkulátor, který vypočítává hlavní kritéria pro hodnocení investic. V této práci jsou také navrženy optimální způsoby investování do realit za daných podmínek pro určité investory.

This thesis deals with analysis of different kinds of investments in the real estate market and compares them from time and financial perspective. There is a programmed calculator for effective comparison that calculates the main criteria for investment rating. There are also drafted optimal investment methods in real estates under given conditions for specific investors.
Investment Real Estate Evaluation with Software Support
Keywords: Investice; nemovitost; daň z převodu; daň z nemovitosti; ceny nemovitostí; software; Investments; Real Estate; Real estate transfer tax; Real Estate Tax; Real Estate Prices; Software